PERANCANGAN SISTEM PELAPORAN KEUANGAN SEDERHANA PADA ORGANISASI NIRLABA - Ni Luh De Erik Trisnawati; Ni Komang Sukreni; Ni Made Rianita (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to assist a non-profit organization in compiling financial reporting automatically through the application of a simple financial reporting system. Orphanage or LKSA is an institution engaged in the social sector which is a non-profit entity. A non-profit organization is an organization that is engaged in community services that does not aim to make a profit (profit) but in its activities also requires funds for its operations so that it requires a financial report. Like other types of non-profit organizations, LKSAs are also required to be able to present reports in an accountable and transparent manner. This research was conducted at LKSA Ananda Seva Dharma which was started by conducting a situation analysis regarding the need for a simple financial application. Furthermore, the researchers designed a simple excel-based financial reporting system and implemented it in the process of preparing LKSA financial reports. The results of the study shows that a simple financial application that has been designed can be used by LKSA Ananda Seva Dharma for the preparation of financial statements so that the preparation of financial statements can be done more easily and efficiently. In addition, the financial statements produced are in accordance with non-profit accounting standards and describe the financial condition of LKSAs in full, so that accountability for the resources provided can be better described through these financial statements.